Studies on the Quality and Heavy Metals in Common Salt Production Using Sea Brine and Sub-Soil Brine in South Tamil Nadu, India - Prema Kumari, P.; Mercy Salima, K.; Ethalsha, P. (Asian Journal of Engineering and Applied Technology, 2015)
The manufacture of common salt using sea brine and sub-soil brine contain several chemical and trace metal elements.This study estimated the salt quality parameters like moisture content, insoluble matter, calcium sulphate, magnesium sulphate, magnesium chloride and sodium chloride content of the salt and also estimated the different trace metals like copper, iron, zinc, manganese and chromium in salts harvested from the Salt samples of two selected salt works, Kovalam SW1 (sea brine) and Puthalam SW2 (sub-soil brine) in Kanyakumari District and the two selected salt works, Vepalodai SW3 (sea brine) and Sahupuram SW4 (sub-soil brine) in Tuticorin District. The salt samples have maximum moisture content in Kanyakumari salt works than Tuticorin District because of the climatic conditions. The salt works using sea brine, harvested salt of the maximum mean sodium chloride content than sub-soil brine using salt works. In both the Districts, sea brine using salt works is having almost similar concentration of heavy metals, likewise sub soil brine using salt works.